1978
DOI: 10.1017/s0014479700008322
|View full text |Cite
|
Sign up to set email alerts
|

Genotype × Environment Interactions in Sorghum Variety Tests in the Sudan Central Rainlands

Abstract: Estimates of variety x environment interactions for grain yield were obtained from a study involving 16 sorghum varieties grown at the same three locations over a 3-year period. Whereas the variety x year interaction was small and not significant, the variety x location and the variety x location x year interactions were highly significant. Evidence was presented suggesting that the years of testing could be reduced by increasing the number of test locations. T.F.M.7 and Karkatib 4/1/1 were identified as desir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

1980
1980
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…They differ somewhat in the basic approaches, and in the criterion used to evaluate accuracy, e.g. Smith (1938), Schultz (1955), Janick (1961), Sokal & Rohlf (1969, Allen, Comstock & Rasmussen (1978), Kambal & Mahmoud (1978), Russell, Russell, Guthrie, Hallauer & Robbins (1978 and Louw (1979), but have in common a decrease· in experimental error.…”
Section: Abocation Of Resources In Sorghummentioning
confidence: 99%
See 3 more Smart Citations
“…They differ somewhat in the basic approaches, and in the criterion used to evaluate accuracy, e.g. Smith (1938), Schultz (1955), Janick (1961), Sokal & Rohlf (1969, Allen, Comstock & Rasmussen (1978), Kambal & Mahmoud (1978), Russell, Russell, Guthrie, Hallauer & Robbins (1978 and Louw (1979), but have in common a decrease· in experimental error.…”
Section: Abocation Of Resources In Sorghummentioning
confidence: 99%
“…To demonstrate the usefulness of having infonnation on the allocation of resources in this experiment, the methods described by Kambal & Mahmoud (1978) and those of Russell e/ al. (1978) were applied.…”
Section: Abocation Of Resources In Sorghummentioning
confidence: 99%
See 2 more Smart Citations
“…He concluded that linear regression methods, if inappropriately applied, are an oversimpli fication of the response of genotype to environment and that multi variate techniques may be a useful alternative when the environments differ by more than one factor. Kambal and Mahmoud (1978) Trenbath (1974a) found no evidence that crop mixtures demonstrated greater intrin sic stability than did the more stable component monoculture.…”
mentioning
confidence: 97%